Khamir Penghasil Indole-3-Acetic Acid dari Rhizosfer Anggrek Tanah Pecteilis susannae (L.) Rafin - Lasmini, Titi; Sutariningsih Soetarto, Endang (Biogenesis: Jurnal Ilmiah Biologi, 2014)
Indole-3-acetic acid (IAA) is a growth hormone produced by plants. Several types of yeast has been reported to produce these hormones, and generally produce IAA in an higher amount than in plants. The purpose of this study is to get the yeast producing indole-3-acetic acid in the rhizosphere soil orchid Pecteilis susannae (L.) Rafin and to test the ability of yeast isolates to form IAA on medium L-tryptophan given as precursors. Yeasts were isolated and tested for their ability to produce IAA in vitro. The results showed that there are four potential yeast isolates that produce IAA which are isolates K2, U5, A3, and A1. Highest concentration of IAA was produced by A3 isolates grown on a medium containing GPB 200 ug / ml of L tryptophan in the amount of 56.262 g/ml.Keywords: Indole-3-acetic acid, rhizosfer yeast, Pecteilis susannae